Manipulasi Linguistik sebagai Instrumen Politik dalam Animal Farm: Sebuah Analisis Wacana Kritis - Parlindungan Pardede; Yumna Rasyid; Miftahulkhairah Anwar (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
Politics and language are inextricably linked, and the relationship between the two has long been the subject of philosophical and linguistic study. Through critical discourse analysis, the contemporary linguistic practice seeks to examine language as a form of social practice. Thus, political discourse is seen as a discourse oriented towards concealing power for manipulative purposes, legitimizing discourse practices, and imposing ideologies. This study analyzes the use of linguistic manipulation in George Orwell's "Animal Farm" using van Dijk's socio-cognitive approach. The results of the study of the text, context, and social cognition dimensions of "Animal Farm" show that the political elites in this novel successfully use linguistic manipulation as an instrument to influence members of society with lower language skills to realize the elites' goals. Linguistic manipulation is also used as an instrument to exercise and maintain power. As a proponent of socialism, Orwell revealed the use of political manipulation in "Animal Farm" as a satire of the Stalin-led socialists who had perverted the goals of the Russian revolution for personal and group gain.